2019
DOI: 10.1108/josm-05-2019-0139
|View full text |Cite
|
Sign up to set email alerts
|

Transformative service research, service design, and social entrepreneurship

Abstract: Purpose The purpose of this paper is to provide an interdisciplinary framework bridging service design and social entrepreneurship with transformative service research (TSR) to create greater synergetic effects to advance wellbeing and drive social impact. Design/methodology/approach This research provides an interdisciplinary review and synthesis of literature to establish a basis for a conceptual framework advancing human wellbeing and driving social impact. Findings The overarching framework created inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 144 publications
1
60
0
1
Order By: Relevance
“…Further, both individual and collective well-being are important (Alkire [Née Nasr] et al, 2020). Just like types of well-being are interactive, it is possible that one level of wellbeing, the other or both can be impacted in a given service context and well-being change at one level will also likely change well-being at the other.…”
Section: Transformative Service and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, both individual and collective well-being are important (Alkire [Née Nasr] et al, 2020). Just like types of well-being are interactive, it is possible that one level of wellbeing, the other or both can be impacted in a given service context and well-being change at one level will also likely change well-being at the other.…”
Section: Transformative Service and Well-beingmentioning
confidence: 99%
“…Within TSR, there is a moral imperative to look beyond the purely economic realities of service systems and to conduct research that has the potential to inform and support positive transformation for individuals, families and communities (Anderson et al, 2013;Rosenbaum et al, 2011). Entrepreneurship, particularly at the micro-level has the potential to be transformative for the poor (Alkire [Née Nasr] et al, 2020). To illuminate this reality, this research qualitatively explores street vending in a multi-cultural, multilocal study to understand how these businesses operate to positively impact individual, collective and societal well-being.…”
Section: Introductionmentioning
confidence: 99%
“…There is a relatively established line of sport management research investigating topics related to the relationship between sport services and well-being (e.g., Dixon & Warner, 2010;Inoue, Sato, Filo, Du, & Funk, 2017;Jang, Ko, Wann, & Kim, 2017;Kim, Kim, Newman, Ferris, & Perrewé, 2019;Sato, Jordan, & Funk, 2015;Westberg & Kelly, 2019). However, due to the absence of a coordinated effort to synthesize this line of research, it has not reached its full potential to make a distinctive contribution, as indicated by a lack of reference to sport services in the broader transformative service research literature (Alkire et al, 2019;Anderson & Ostrom, 2015;Russell-Bennett, Fisk, Rosenbaum, & Zainuddin, 2019). By introducing the terminology of TSSR and displaying high-quality TSSR scholarship through the flagship sport management journal, we have aimed to provide an overarching framework for this research area and to facilitate coordination to produce knowledge that is highly impactful within and beyond the sport management literature.…”
mentioning
confidence: 99%
“…TSR distinguishes itself from other service research in relation to the outcomes that it investigates (Alkire et al, 2019). TSR emphasizes the importance of indicators of increasing and decreasing well-being, like physical health, mental health, financial well-being, discrimination, literacy and access (Anderson and Ostrom, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We live and work within service systems, such as families or schools (Alkire et al, 2019) and consumers engage in services on a daily basis, interacting with a variety of service providers such as financial firms, healthcare providers and retailers (Anderson et al, 2013). Therefore, services have the potential to affect the social and economic world within which we live (Nasr and Fisk, 2019) and can have a positive or negative impact on consumer well-being (Anderson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%